Treating hepatitis C virus in children: time for a new paradigm - Claire Thorne; Giuseppe Indolfi; Anna Turkova; Carlo Giaquinto; Eleni Nastouli (Elsevier, 2015)
Hepatitis C virus infection is a leading cause of liver-related morbidity and mortality. In the paediatric population, HCV infection is underdiagnosed and undertreated in the absence of robust screening policies worldwide, and a lack of tolerable, effective treatment. The recent advances in HCV drug development allow for optimism, a change in outcomes for the millions of children infected with this virus and a unique opportunity for strategies aiming at HCV eradication. The rapid development of the new compounds has been followed by a welcome shift in the regulatory processes; however, strategies aiming at improving diagnosis, selecting the best combinations and addressing mother-to-child transmission issues are required for the new therapeutic agents to be introduced safely and effectively in the paediatric population and to contribute to the goal of virus eradication.